Instance-based networking a communication paradigm for mobile applications. - Youssef, Moustafa (Mobile computing and communications review.)
In this work we consider the design principles of the Instance-Based Network (IBN), an extended version of a generic Content-Based Network (CBN). IBN acts as an overlay communication platform over which end-point entities, called contents, communicate independently from their physical locations while providing the flexibility of having different instances of the same content. The semantics of different instances are assigned by the application using the IBN. Routing in the IBN is instance-based; the IBN can route a message to a specific content instance or to the closest instance, if no exact match is found for the destination content instance.